Glossolalia: ética e dimensão simbólica no pentecostalismo - Ricci, Maurício (Faculdade de Ciências e Letras - Unesp - Araraquara., 2017)
This article analyses the simbólical mediations in the Pentecostalism churchs, specialy, the glossolalia — the gift of tongues, the most important subject within the Pentecostal Theology. The devoted believes that the gift of tongues is the explicited evidence of Holy Ghost's baptism, and they build their identity and their alterity by means of this gift.